Carcinoid tumours of the bronchus: a 33 year experience. Issue 8 (August 1984) - Hurt, R; Bates, M
Abstract : The term adenoma of the bronchus is discussed, and 79 cases of bronchial carcinoid seen from 1951 to 1983 are reviewed. The symptoms, radiological findings, and bronchoscopic appearances are described. There was no case of the carcinoid syndrome. In no case did haemorrhage cause any serious problem after biopsy at rigid bronchoscopy. In three patients the tumour was reported to be an oat cell carcinoma-in two on the basis of material obtained at fibreoptic bronchoscopy. Resection was by pneumonectomy in 10 cases, lobectomy in 52, segmentectomy in six, a bronchoplastic procedure without resection of lung in seven cases, enucleation in two, and a wedge resection in one case. There was one case of atypical carcinoid which was found at operation to be unresectable. A 5-30 year follow up in 57 cases revealed a recurrence of tumour in two cases, nine and 16 years after lung resection. No recurrence occurred in the nine cases treated by conservative bronchial resection with conservation of lung tissue. An actuarially assessed life table analysis shows survival rates of 94% after 10 years, 80% after 15 years, and 64% after 25 years without recurrence. The similarity of carcinoid to oat cell carcinoma is noted and the serious clinical implications of this are analysed, especially in view of the increasing use of fibreoptic bronchoscopy. The malignant potential of carcinoid and the extent of pulmonary resection is discussed. It is concluded that a carcinoid tumour of the lung has only slight malignant potential and that it may be treated by bronchotomy or sleeve resection of the bronchus in suitable cases. If serious infective changes have occurred in the lung distal to the tumour or if the tumour has extended into the lung parenchyma (88% of cases in this series) lung resection will be necessary. The follow up period should be for at least 25 years, in view of the incidence of late recurrence.